Poverty moderates the association between gender and school dropout in South African adolescents - Boyes, M; Berg, V; Cluver, L (Taylor and Francis, 2017)
This study examined prospective associations between poverty, gender, and school dropout in a large community sample of South African adolescents (baseline: n = 3515, follow-up: n = 3401, 57% female, age range at baseline: 10–17 years, mean age at baseline = 13.45). School dropout was defined as being enrolled in school at baseline assessment but no longer enrolled in school at follow-up assessment. Poverty was measured at baseline assessment using an index of access to the eight highest socially perceived necessities for South African children and adolescents. Demographic characteristics including child gender and age, province, and urban versus rural location were recorded at baseline assessment and controlled for in the analysis. As predicted, higher poverty scores (AOR = 2.01, p < .001) were associated with increased odds of school dropout 1 year later. Gender was not a significant predictor of school dropout (AOR = 1.56, p = .07) but did interact with poverty (AOR = 0.66, p = .04) in predicting school dropout. However, our initial hypothesis that the impact of poverty on school dropout would be stronger for girls than boys was not supported. Instead, results indicated that while girls were at elevated risk of school dropout at low and mean levels of poverty, at high levels of poverty this gender difference was no longer evident. Findings suggest that vulnerable boys should not be neglected in policies to improve retention in education in contexts of extreme poverty.